Systems of care for ambulatory management of decompensated heart failure - Badrish, Narotham; Sheifer, Stuart; Rosner, Carolyn M. (Frontiers in Cardiovascular Medicine, 2024)
Heart failure (HF) represents a worldwide health burden and the annual per patient cost to treat HF in the US is estimated at 24,383, with most of this expense driven by HF related hospitalizations. Decompensated HF is a leading cause for hospital admissions and is associated with an increased risk of subsequent morbidity and mortality. Many hospital admissions for decompensated HF are considered preventable with timely recognition and effective intervention.Systems of care that include interventions to facilitate early recognition, timely and appropriate intervention, intensification of care, and optimization to prevent recurrence can help successfully manage decompensated HF in the ambulatory setting and avoid hospitalization.